2020
DOI: 10.3390/nu12123799
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Cholecalciferol Booster Therapy is Associated with a Reduced Risk of Mortality in Patients with COVID-19: A Cross-Sectional Multi-Centre Observational Study

Abstract: The worldwide pandemic of 2019 novel coronavirus disease (COVID-19) has posed the most substantial and severe public health issue for several generations, and therapeutic options have not yet been optimised. Vitamin D (in its “parent” form, cholecalciferol) has been proposed in the pharmacological management of COVID-19 by various sources. We aimed to determine whether COVID-19 mortality was affected by serum 25-hydroxyvitamin D (25(OH)D) levels, vitamin D status, or cholecalciferol therapy, and to elucidate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(125 citation statements)
references
References 22 publications
2
101
0
14
Order By: Relevance
“…In previous studies, hospitalized patients with COVID-19 receiving vitamin D3 [20,21] or calcifediol [42] showed a less severe outcome of disease as compared to those not receiving vitamin D supplements. Moreover, a high-dose oral vitamin D supplementation helped to achieve SARS-CoV-2 RNA negativity in greater proportion of asymptomatic vitamin D-deficient individuals with SARS-CoV-2 infection along with a significant decrease in inflammatory markers [43].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In previous studies, hospitalized patients with COVID-19 receiving vitamin D3 [20,21] or calcifediol [42] showed a less severe outcome of disease as compared to those not receiving vitamin D supplements. Moreover, a high-dose oral vitamin D supplementation helped to achieve SARS-CoV-2 RNA negativity in greater proportion of asymptomatic vitamin D-deficient individuals with SARS-CoV-2 infection along with a significant decrease in inflammatory markers [43].…”
Section: Discussionmentioning
confidence: 87%
“…Some studies provided evidence that subjects exposed to vitamin D deficiency may develop a more severe COVID-19 [13][14][15][16], whereas other studies failed to find such an association [17][18][19]. Moreover, the effects of vitamin D supplementation on clinical outcome of COVID-19 is still a matter of uncertainty [20][21][22]. Variability in clinical end-points may explain the heterogeneity of results of these studies evaluating the impact of hypovitaminosis D and its treatment on COVID-19 outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Although this study received significant criticism from the National Institute for Health and Care Excellence (NICE) in the UK [159], an independent follow-up statistical analysis supported the findings of the study with respect to the results of cholecalciferol treatment [160]. Another trial of 986 patients hospitalized for COVID-19 in three UK hospitals administered cholecalciferol supplementation (≥ 280,000 IU in a time period of 7 weeks) to 151 patients and found an association with a reduced risk of COVID-19 mortality, regardless of baseline 25-hydroxyvitamin D levels [161]. However, a double-blind, randomized, placebo-controlled trial of 240 hospitalized COVID-19 patients in São Paulo, Brazil administered a single 200,000 IU oral dose of vitamin D. While levels of 25-hydroxyvitamin D did increase from 21% to ~27% (p = 0.001) and the supplementation was well tolerated, there was no reduction in the length of hospital stay or mortality and no change to any other relevant secondary outcomes [162].…”
Section: Vitamin Cmentioning
confidence: 60%
“…Namely, since time when the possible favorable effects of vitamin D3 in COVID-19 patients have been proposed 14,15 , several well designed and convincing studies have clearly shown association between vitamin D deficiency and more severe COVID-19 clinical manifestations [16][17][18][19][20]46 . Recent interventional studies provide further evidence on beneficial and protective impact of vitamin D3 among COVID-19 patients [21][22][23][24] . Protective vitamin D3 mechanisms in COVID-19 patients are presumed to be multiple, including potent immunomodulatory activity, antiviral peptide induction, enhancement of physical barrier integrity and even direct interference with viral replication [13][14][15]47 .…”
Section: Discussionmentioning
confidence: 99%
“…Namely, many "pre-corona" studies have found antiviral, immunomodulatory, and anti-inflammatory properties of vitamin D3 13 , suggesting this data could be extrapolated to SARS-CoV-2 infection 14,15 . Assumptions on beneficial effects of vitamin D3 in COVID-19 patients have recently been verified by several convincing clinical and interventional studies [16][17][18][19][20][21][22][23][24] . The importance of this topic is highlighted by data showing that the global pandemic of hypovitaminosis Dis being ongoing concomitantly with the COVID-19 pandemic [25][26][27][28] .…”
Section: Introductionmentioning
confidence: 87%